Antimicrobial resistance patterns of Escherichia coli isolated from raw cow milk and, from clinical specimens in a tertiary institution, Uganda – A cross sectional study - Jacob Michael Othieno; Anastacia Sebbowa Nabyonga; Abel Wembabazi; Brian Martin Odhiambo; Winnie Nalwanga; Amusa Wamawobe; Sabrina Bakeera-Kitaka; Beatrice Achan (PLoS ONE, 2026)
Background Inappropriate antibiotic use in animal husbandry contributes to the emergence of resistant bacteria, which may enter the human population through the food chain. Objective To compare antimicrobial resistance (AMR) patterns of Escherichia coli isolated from raw cow milk in Kawempe Division, Kampala, with those from clinical specimens processed at Makerere University Laboratory, Kampala, Uganda. Methodology A cross-sectional study from January to June 2024 on 40 E. coli isolates from 124 raw cow milk samples, alongside 40 clinical E. coli isolates was conducted. Antibiotic susceptibility was tested using the Kirby Bauer disk diffusion method against 11 antibiotics. Differences in resistance between milk and clinical isolates were assessed using chi-square analysis. Results Of the 124 milk samples (77 from cans, 47 from packs), E. coli was isolated from 40/124 (32.26%), with most 39/124 (31.45%) from cans and only 1/124 (0.81%) from a pack. Antibiotic resistance profiles of E. coli isolates (n = 40) from milk samples showed the highest resistance to ampicillin (32.5%), followed by cotrimoxazole (22.5%), ceftriaxone (5%), Cefotaxime; (5%) and, cefuroxime (5%). Multidrug resistance (MDR) and extended-spectrum β-lactamase (ESBL) production were detected in 5% milk isolates. Clinical isolates; n = 40; exhibited higher resistance to cotrimoxazole (95%), ampicillin (87.5%), cefuroxime (72.5%), ceftriaxone (70%), ceftazidime (57.5%), ciprofloxacin (55%), and cefotaxime (52.5%), with lower resistance to amoxicillin–clavulanate (27.5%), chloramphenicol (25%), and gentamicin (22.5%). Emerging resistance to imipenem was observed (20%). MDR and ESBL prevalence among clinical isolates were 85% and 70%, respectively. Resistance was significantly higher in clinical isolates than in milk isolates (p < 0.001). Conclusion This study shows a much higher burden of resistance, MDR, and ESBL production in clinical than milk-derived Escherichia coli . At the same time, the similar resistance patterns observed for commonly used antibiotics such as ampicillin and cotrimoxazole suggest a possible overlap between human and animal reservoirs. These findings highlight the need for context-specific antimicrobial stewardship strategies in both the health and diary sector.